2008
DOI: 10.1074/jbc.m710128200
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles for the C-terminal Tail of the Chemokine Scavenger D6

Abstract: D6 is a heptahelical receptor that suppresses inflammation and tumorigenesis by scavenging extracellular pro-inflammatory CC chemokines. Previous studies suggested this is dependent on constitutive trafficking of stable D6 protein to and from the cell surface via recycling endosomes. By internalizing chemokine each time it transits the cell surface, D6 can, over time, remove large quantities of these inflammatory mediators. We have investigated the role of the conserved 58-amino acid C terminus of human D6, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 50 publications
4
78
1
Order By: Relevance
“…In this study, we demonstrate for the first time that stimulation of CCX-CKR with CCL19, CCL21, and CCL25 indeed induced ␤-arrestin2-GFP translocation. CCX-CKR did not translocate ␤-arrestin2-GFP in the absence of chemokines, which is in contrast to the constitutively phosphorylated chemokine decoy receptor D6 (21). Moreover, fluorescently labeled CCL19 co-localized in the same intracellular vesicles as ␤-arrestin2-GFP, suggesting recruitment of ␤-arrestin to CCL19-bound CCX-CKR.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, we demonstrate for the first time that stimulation of CCX-CKR with CCL19, CCL21, and CCL25 indeed induced ␤-arrestin2-GFP translocation. CCX-CKR did not translocate ␤-arrestin2-GFP in the absence of chemokines, which is in contrast to the constitutively phosphorylated chemokine decoy receptor D6 (21). Moreover, fluorescently labeled CCL19 co-localized in the same intracellular vesicles as ␤-arrestin2-GFP, suggesting recruitment of ␤-arrestin to CCL19-bound CCX-CKR.…”
Section: Discussionmentioning
confidence: 83%
“…D6 constitutively recruits ␤-arrestin, which is essential for the observed continuous internalization of D6 (20). However, a more recent study provided evidence that ␤-arrestin was not necessarily involved in D6 internalization but increased receptor stability (21). CCX-CKR has been previously suggested to internalize CCL19 in a ␤-arrestin-independent manner (10).…”
mentioning
confidence: 99%
“…Importantly, the constitutive internalisation and recycling of D6 is associated with, although apparently not dependent on, ligand-independent constitutive phosphorylation of the C-terminal portion of the molecule [55,59]. Removal of the most C-terminal 44 amino acids, or mutation of 6 serine residues in this region, results in a block in phosphorylation but surprisingly has little effect on ligand internalisation by D6 [59]. It is still not clear why such large amounts of D6 are present within the cells with only relatively low representation on the cell surface.…”
Section: In Vitro Studies Of D6 Functionmentioning
confidence: 99%
“…We, and others, have demonstrated that D6 binds ligand at the cell surface and then internalises it in a Rab5-dependent manner via the recycling endosomal system before depositing it in acidic lysosomes for intracellular degradation [56,57]. Indeed D6 is capable of constitutively internalising and recycling, a process that may be dependent on b-arrestin [58] although the precise role for arrestins in the function of D6 remains to be resolved [59]. Importantly, the constitutive internalisation and recycling of D6 is associated with, although apparently not dependent on, ligand-independent constitutive phosphorylation of the C-terminal portion of the molecule [55,59].…”
Section: In Vitro Studies Of D6 Functionmentioning
confidence: 99%
See 1 more Smart Citation